Inheritance of common bean resistance to wilt caused by Curtobacterium flaccumfaciens pv. flaccumfaciens - Valentini, Giseli (2011)
The objective of this work was to determine the inheritance of resistance in common bean to wilt of Curtobacterium. Two experiments were carried out: in the first one, five common bean genotypes with different resistance reactions to wilt of Curtobacterium were crossed in diallel arrangement; and in the second one two crosses between resistant and susceptible genotypes – IAC Carioca Aruã x SCS Guará and IAC Carioca Pyatã x Pérola – were carried out in order to give rise to the generations P1, P2, F1, F2, RC1 and RC2. In both experiments, the common bean resistance to bacterial wilt was evaluated through the inoculation of the Cff 2634 isolate. The diallel analysis showed that although non-additive and additive effects are involved, there was a greater participation of the genes with additive effect on the genetic control of the inheritance of resistance to bacterial wilt, which shows the possibility of improvement through selection. The inheritance of resistance to wilt of Curtobacterium is complex, with more than three genes involved and a narrow-sense heritability of 29% for 'IAC Carioca Aruã' x 'SCS Guará' cross and 44% for 'IAC Carioca Pyatã' x 'Pérola' cross.